The Effect of Brand Image, Price Perception, and Product Quality on the Purchase Decision of Ms Glow Skincare on Students of the National University of Jakarta Selatan - Rahayu Lestari; Lilis Suryani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of brand image, price perception, and product quality on the purchasing decision of MS Glow Skincare for South Jakarta National University students. Sources and research data using primary data in the form of a questionnaire, this research data was given to 100 respondents. The research sample was taken using purposive sampling. The analytical method used is Partial Least Square (PLS) with the help of the SmartPLS 3.0 application. The results of the study partially found that there was a positive and significant effect of brand image on purchasing decisions for Ms. Glow Skincare for National University students, there was a positive and significant influence on product quality on purchasing decisions for Ms. Glow Skincare for National University students, there was a negative and significant influence on price perception on decisions. Purchase of Ms. Glow Skincare for National University students